Determinants of pull strength in captive grey mouse lemurs. (22nd October 2015) - Thomas, P.; Pouydebat, E.; Brazidec, M. L.; Aujard, F.; Herrel, A.
Abstract: Grasping is important for arboreal species as it allows them to hold on to branches. Although grasping has been studied previously in the context of primate origins and as an indicator of age‐induced loss in overall performance, little is known about the proximate determinants of variation in strength. We measured hand pull strength in 62 adult captive individuals of grey mouse lemurs Microcebus murinus of known age. In addition, we measured the body mass and the length of the forearm in each individual. Our results showed that animals with a longer ulna, and animals that weighed more, and had a greater relative body mass had higher pull strength. However, despite the fact that females are bigger than males, differences in pull strength were not significantly different between the two sexes. Although comparative data for other species of vertebrates are scarce, our data suggest that mouse lemurs have relatively high pull strength for their size that may be interpreted as an adaptation to arboreal locomotion.